International Student's Language Learning Identities in English as a Lingua Franca Context in Indonesia - Komilie Situmorang; Dwi Yulianto Nugroho; Michael Recard Sihombing (Yayasan Visi Intan Permata, 2021)
Indonesia has stipulated the implementation of the international program as one of its internationalisation's agendas. As a result, private and public universities strive to create international programs that would attract international students. This study focuses on an international program in a private university in Tangerang, which promotes English as a medium of instruction with little interference from native speakers. As many previous research have centred around study abroad in English speaking countries, this study offers a novelty of how identities are constructed in the context of English as a Lingua Franca where both local Indonesian and the international students are non-native speakers of English. Therefore, this research aims to discover how international students construct their language learning identity in English as a Lingua Franca context in Indonesia. There were eight participants from five different countries. They were interviewed using conversational narrative interview, and the data was analysed using narratives analysis. The findings were established in themes, and they indicated the positive identities constructions in many ways. These included reconstructing economic identity to religious identity, establishing Lingua Franca speakers identities, constructing global citizenship identities where all these constructions were supported by the acceptance and the zero pressure from the host. Therefore, it is concluded that zero power inequality promotes favourable language learning and identity construction during study abroad.